Quality of Public Physical Activity Resources and its Association with Frequency of Use in Two Low-Income Neighborhoods in Brazil. (19th September 2022) - Reis, Arianne C.; Mortimer, Taylor; Vieira, Marcelo C.; Pessanha de Freitas, Vera; Sperandei, Sandro
Abstract: This cross-sectional study reports on the relationship between objectively-assessed quality of physical activity resources (PARs) and frequency of use within two low income neighborhoods in Rio de Janeiro, Brazil. The Physical Activity Resource Assessment was used to assess the quality of all PARs of the two neighborhoods ( n = 60). Frequency of use was assessed by direct observation. The quality of PARs and frequency of use was both found to be very low, but the higher quality PARs received higher number of users. An interaction between sex, age and use of PARs was found, with females and older adults significantly less present. Homicide rates in the vicinity of PARs did not contribute to lower levels of use. In conclusion, if we are to successfully promote higher levels of leisure-time physical activity among the population, care needs to be taken with the design and maintenance of these spaces.